Work-related technology use during nonwork time and its consequences: A resource-oriented perspective - Svenja Schlachter; Ilke Inceoglu; Almuth McDowall; Mark Cropley (Journal of Occupational and Organizational Psychology, 2025)
Employees increasingly use information and communication technologies (i.e., ICTs) to work during nonwork time (e.g., responding to e-mails, taking calls), even when not contractually required. Despite potential work-related benefits, voluntary work-related ICT use can affect employees' recovery and well-being. Drawing on the conservation of resources theory and self-regulation, we argue that engaging in voluntary ICT use during workday evenings is a work-related resource investment, requiring self-regulatory resources. Consequently, employees lack such resources to regulate their attention away from work, thus experiencing reduced psychological detachment. This, in turn, can impede employees' ability to engage in mood repair regarding affective well-being at bedtime and the following morning. We propose that employees can alleviate this process through substituting and replacing self-regulatory resources by having control over their evening and good sleep quality, respectively. Conducting a daily diary study over five consecutive workdays and following mornings with 187 participants, we found negative indirect effects of voluntary ICT use on affective well-being the following morning, via reduced psychological detachment. Feeling in control during nonwork time and sleep quality mitigated these effects. Our study contributes to the conceptual understanding of voluntary ICT use and how this behaviour can be managed more actively by individuals.
Keywords: 650; nonwork time; recovery; resources; well-being; work-related technology use